Pengendalian Material Sisa Pada Pembangunan Gereja GBKP Desa Bukit - Asri Afriliany Surbakti; Mei Brilian Harefa; Nobertus Giawa (Universitas Quality, 2022)
The implementation of construction projects requires the use of many natural resources, one of which is construction materials. Construction materials should be well planned, from the process of planning, implementing, and controlling. By doing construction material management, it will minimize the presence of residual materials and residual materials are also not wasted. Management of residual materials from construction projects can be done with the stages of reduse (preventing / reducing), reuse (reuse), recycle (recycling), and salvage (moving). The GBKP Bukit Village church construction project is the object of this study. The purpose of this study is to find out the materials that are most often associated with the church project and to find out what are the controls carried out by construction actors to minimize the presence of residual material. The method used is to provide questionnaires to construction actors to obtain data, then the data is processed with the percentage description method to find out the most frequently residual materials and what residual material control is carried out by the contractor. The results of this study show that reinforcing iron is the material that most often occurs in construction projects. Meanwhile, control of residual materials by recycling is rarely carried out by construction actors in this project because in general construction actors have not felt it is important to recycle construction materials. In addition, construction actors' knowledge of recycling construction materials is also not enough, so construction actors feel that it is better to sell the remaining materials that can be recycled to third parties.